Gastroesophageal reflux disease in idiopathic pulmonary fibrosis: uncertainties and controversies - Wang, Zheng; Kreuter, Michael (Respiration, 2018)
The mechanisms of idiopathic pulmonary fibrosis (IPF), a rare, devastating disease with a median survival of 3-5 years, are not fully understood. Gastroesophageal reflux disease (GERD) is a frequent comorbidity encountered in IPF. Hypothetically, GERD-associated microaspiration may lead to persistent inflammation impairing lung infrastructure, thereby possibly accelerating the progression of IPF. IPF may increase intrathoracic pressure, which can aggravate GERD and vice versa. On the basis of the possible beneficial effects of antireflux or antacid therapy on lung function, acute exacerbation, and survival, the recent international IPF guideline recommends antacid therapies for patients with IPF, regardless of symptomatic GERD. However, due to newer conflicting data, several national guidelines do not support this recommendation. Elucidation of these questions by further clinical and bench-to-bedside research may provide us with rational clinical diagnostic and therapeutic approaches concerning GERD in IPF. The present review aims to discuss the latest data on the controversial association of IPF and GERD.
Gesehen am 24.06.2019